The methodology of computer-aided design of means of measuring the integral purpose - Бабак, В.П.; Квасників, В.П.; Ларін, В.Ю. (Proceedings of National Aviation University (archive), 2007)
In article is offered a principle of building and achievement of a technical devises of technological parameters control of travel, location, speed etc on basis of computer-aided design system methods is developed of authors.